(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
The purpose of the state financial control event in public sector entities is to reveal the organization’s financial indicators and status, and to ensure the rational use of funds allocated from the state budget. Currently, the internal audit activity in budget organizations is expanding. This consists in making recommendations based on the cost estimates in the organization, and is aimed at timely elimination of errors and deficiencies that occur in the organization. Also, this article highlights the differences and common aspects of both types of control.